Pengaruh Earning Per Share (Eps), Dividend Per Share (Dps), Dan Price Earning Ratio Per Terhadap Harga Saham Perusahaan Manufaktur Tahun 2010-2013 Di Bursa Efek Indonesia BEI - Widyowati, Linda, Agus Muqorrobin, Drs., M.M (2015)
This study aims to determine the effect of variable Earning Per Share (EPS) Dividend Per Share (DPS), and Price Earning Ratio (PER) on stock prices. The research sample totaled 16 in companies listed on the Indonesian Stock Exchange (BEI) by the amount of data as much as 64 to the period 2010-2013. The data used came from ICMD (International Capital Market Directory) taken at the Muhammadiyah University of Surakarta.The sampling technique used purposive sampling techniques or retrieval of data in accordance with the criteria used in this study. The method of analysis used in this study with descriptive analysis, multiple linear regression analysis, the classical assumption test is used to assess the validity of the regression equation including normality test, multicollinearity test, autocorrelation test, and test heterokesdatisitas. In addition there is also a hypothesis test using t test, F test at the significant level of 0.05 and a coefficient of determination. Based on the analysis F test has been done, the variable Earning Per Share (EPS) Dividend Per Share (DPS), and Price Earning Ratio (PER) jointly effect on stock prices as calculated F value of 251.743 with a significance value of 0.000. This indicates that the calculated value is much less significant than the significant value of the specified standard. Based on the coefficient of determination that has been done can be obtained gasil value of 0.926. That is 92.6% stock price may be affected by variables Earning Per Share (EPS) Dividend Per Share (DPS), and Price Earning Ratio (PER). While the remaining 7.4% is influenced by variables or other factors. Keywords: Earning Per Share (EPS) Dividend Per Share (DPS), Price Earning Ratio (PER), Price Stock.